Ectopic paraesophageal mediastinal parathyroid adenoma, a rare cause of acute pancreatitis - Foroulis, Christophoros N (BioMed Central, 2004)
BACKGROUND: The manifestation of primary hyperparathyroidism with acute pancreatitis is a rare event. Ectopic paraesophageal parathyroid adenomas account for about 5%–10% of primary hyperparathyroidism and surgical resection results in cure of the disease. CASE PRESENTATION: A 71-year-old woman was presented with acute pancreatitis and hypercalcaemia. During the investigation of hypercalcemia, a paraesophageal ectopic parathyroid mass was detected by computerized tomography (CT) scan and (99m)Tc sestamibi scintigraphy. The tumor was resected via a cervical collar incision and calcium and parathormone tumor levels returned to normal within 48 hours. CONCLUSIONS: Acute pancreatitis associated with hypercalcaemia should pose the suspicion of primary hyperparathyroidism. Accurate preoperative localization of an ectopic parathyroid adenoma, by using the combination of (99m)Tc sestamibi scintigraphy and CT scan of the neck and chest allows successful surgical treatment.